2018
DOI: 10.1145/3274435
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Urban Tourism Space Digitally

Abstract: Over the past decade, Airbnb has emerged as the most popular platform for renting out single rooms or whole apartments. The impact of Airbnb listings on local neighborhoods has been controversially discussed in many cities around the world. The platform's widespread adoption led to changes in urban life, and in particular urban tourism. In this paper, we argue that urban tourism space can no longer be understood as a fixed, spatial entity. Instead, we follow a constructionist approach and argue that urban tour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Collaboration in developing tourism destinations can also be conducted using social media applications, and every smartphone user has a social media account (Adi and Heripracoyo, 2018). Since the tourism industry cannot stand alone, good cooperation is needed for promoting and marketing digital tourism (Stors and Baltes, 2018). In addition, this study explains potential future research regarding four topics, namely, millennials, marketing strategy, metaverse tourism and virtual tours which are quite far apart and not connected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaboration in developing tourism destinations can also be conducted using social media applications, and every smartphone user has a social media account (Adi and Heripracoyo, 2018). Since the tourism industry cannot stand alone, good cooperation is needed for promoting and marketing digital tourism (Stors and Baltes, 2018). In addition, this study explains potential future research regarding four topics, namely, millennials, marketing strategy, metaverse tourism and virtual tours which are quite far apart and not connected.…”
Section: Resultsmentioning
confidence: 99%
“…Examples are TripAdvisor, Airbnb, MakeMy Trip and other local apps. Additionally, the benefits of digital tourism attract tourists to digital experiences by building an environment that can be conducted interactively (Stors and Baltes, 2018). Innovation, especially with information technology, has a positive impact on several sides of tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the exponential growth of tourism in cities in the past decade and the characteristics of this tourism have caused significant adverse impacts, especially on historical centres and their residents (Dodds & Butler, 2019). The process of touristification (Bianchi, 2003;Stors & Baltes, 2018) is exacerbated by the concentration of tourism in historical centres, which results in the relocation of traditional activities (Coccossis & Mexa, 2002;UNWTO, 2005) and local businesses (Gy odi, 2019). Thus, tourists concentrate on specific areas in their search for authenticity (Zukin, 2016), generating a new urban landscape that endangers the cities heritage, not only from a physical preservation perspective but also from a possible loss of uniqueness (Barrera-Fern andez, Hern andez-Escampa, & Balbuena, 2016).…”
Section: The Impact and Repercussions Of Tourism In Urban Communitiesmentioning
confidence: 99%
“…In Private and shared rooms, guests care about host friendliness (Lee, 2022). In a study by Stors and Baltes (2018), it was found that hosts encourage their guests to visit places in their neighborhood, leading to the promotion of local tourism. Accordingly, customers value their interaction with hosts; thus, to improve customer satisfaction, Airbnb hosts should interact with guests and respond to guests’ inquiries quickly (Zhang, 2019a, b).…”
Section: Analysis and Findingsmentioning
confidence: 99%